2015
DOI: 10.1016/j.physbeh.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social isolation and enriched environment during adolescence on voluntary ethanol intake and anxiety in C57BL/6J mice

Abstract: This study was designed to determine the impact of an enriched environment in a previously established stress model of isolation during early development that induces high alcohol (ethanol) self-administration. The study was conducted with male and female C57BL/6J mice housed in isolation or in groups that were either provided or withheld enrichment during adolescence. The impact of these housing conditions was assessed during adulthood by measuring weight gain, quantifying voluntary ethanol intake, measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 49 publications
9
65
5
Order By: Relevance
“…While Rockman et al [21] showed that rats reared under EE conditions exhibited an increase in voluntary ethanol consumption, Deehan et al [22] found decreased ethanol consumption, preference, and motivation to obtain ethanol in the operant self-administration paradigm in alcohol-preferring rats reared under similar EE conditions. Other studies showed that EE can reduce ethanol consumption and ethanol-induced CPP [23, 24], as well as protect adolescent single-housed mice from increasing ethanol intake during adulthood [25]. …”
Section: Introductionmentioning
confidence: 99%
“…While Rockman et al [21] showed that rats reared under EE conditions exhibited an increase in voluntary ethanol consumption, Deehan et al [22] found decreased ethanol consumption, preference, and motivation to obtain ethanol in the operant self-administration paradigm in alcohol-preferring rats reared under similar EE conditions. Other studies showed that EE can reduce ethanol consumption and ethanol-induced CPP [23, 24], as well as protect adolescent single-housed mice from increasing ethanol intake during adulthood [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Even though the authors attributed this finding to the stress of social conflict upon grouping (e.g., Norman et al ., 2015), the study nevertheless led to a systematic development into how social versus isolate housing can alter voluntary ethanol drinking. Studies in laboratory rodents have led to a general consensus that isolate housing leads to increased ethanol drinking (Deatherage, 1972; Parker & Radow, 1974; Schenk et al, 1990; Wolffgramm, 1990; Hall et al ., 1998; Núñez et al ., 2002; Juárez & Vázquez-Cortés, 2003; Doremus et al ., 2005; Advani et al ., 2007; Deehan et al ., 2007; Ehlers et al ., 2007; McCool and Chappell, 2009; Lopez et al ., 2011; Chappell et al ., 2013; Talani et al ., 2013; Butler et al ., 2014; Lopez & Laber, 2015). However, there are exceptions to these observations; for example, socially paired laboratory rats (McCusker and Bell, 1988; Adams & Oldham, 1996; Tomie et al ., 2005; Varlinskaya et al ., 2015) and mice (Logue et al ., 2014) exhibit increased voluntary ethanol consumption depending on the precise experimental conditions and measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Although social isolation is reported to increase anxiety-like measurements on the elevated-plus-maze [44,45], this finding is not always confirmed [46]. In fact, group housing of mice during adolescence was reported to increase anxiety-like behavior in the light-dark test [47].…”
Section: Discussionmentioning
confidence: 93%